PEMILIHAN BUPATI BENGKALIS DI LEMBAGA PEMASYARAKATAN KELAS II A DALAM MASA PANDEMI COVID-19 - Shakila, Wella Afra; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
General elections are a means of democracy to form a system of state power that is sovereign by the people and representative deliberations outlined by the 1945 Constitution. The central government has issued Law Number 7 of 2017 concerning General Elections. In 2020, Bengkalis Regency will return to carrying out the duties of the people by carrying out the 2020 Bengkalis Regent and Deputy Regent Elections. The election held this time is far different from the previous Pilkada, this is because it was the first time the Pilkada was held in the midst of the Covid-19 pandemic. With regard to the Simultaneous Pilkada in 2020 which also coincided with the occurrence of the Covid-19 Pandemic, the government is swift and has the right thinking and anticipates that the Pilkada will continue and be carried out properly. This study aims to determine the mechanism for the election of the Regent of Bengkalis Regency in Class II A Correctional Institutions during the Covid-19 pandemic. The type of research used is descriptive qualitative research, while the data collection techniques used are interviews and documentation. While the informants in this study were 8 people, namely Disdukcapil, KPUD officers, Bawaslu, Deputy Head of Bengkalis Class II A Prison, Supervisory Committee officers and Prisoners. The data used are primary data and secondary data, data analysis techniques with data reduction, data presentation and verification. Based on the results of the research that has been carried out, it was found that the implementation of the Bengkalis Regency Regent Election in Class II A Correctional Institutions during the Covid-19 pandemic went according to existing regulations. However, in terms of the mechanism, there are still several mechanisms that have not gone well, namely the limited implementation of the campaign due to the Covid-19 Pandemic, and the large number of convicts who cannot vote for several reasons, namely the lack of political educational background and some of the convicts who are constrained because of their identity. who were detained when they were prisoners in the prison before. Keywords: Regional Head Election, Covid-19 Pandemic